Interaksi Indeks Dow Jones, Kurs Dolar, Minyak Dunia, Emas dan Indeks Saham Indonesia LQ45 - Muh. Irfandy Azis; Sabrang Gilang Gemilang; Dzulfikri Azis Muthalib (Politeknik Negeri Batam, 2020)
This study aims to determine the short-term effect, long-term effect and causality effect between the Dow Jones Index, Dollar Exchange Rate, Crude Oil WTI and Gold on the Indonesian Stock Index LQ45. The type of data used to achieve the research objectives is time series data with daily data starting from January 1, 2010 to December 31, 2019. The data is processed using the e-views application, so the results of the cointegration test show that there is a cointegration relationship in each research variable can be interpreted that there is a long-term effect between the Dow Jones Index, Dollar Exchange Rate, Crude Oil WTI and Gold on the Indonesian Stock Index LQ45. Based on the results of the Granger causality test, it shows that there is a two-way causality effect between the Dollar Exchange Rate and Gold against the Indonesian Stock Index LQ45. Whereas the Dow Jones Index and Crude Oil WTI only have a one-way effect to the Indonesian Stock Index LQ45. In addition, based on the results of the impulse response analysis by taking ten observation periods, it was found that at the beginning of the observation period there was a large effect then it got smaller as the observation period increased but still had an effect on each research variable. This means that there is a long-term effect between the Dow Jones Index, Dollar Exchange Rate, Crude Oil WTI and Gold on the Indonesian Stock Index LQ45.